2021
DOI: 10.3390/polym13142295
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Drug-Eluting Polycaprolactone/poly(lactic-co-glycolic Acid) Prolapse Mats Using Solution-Extrusion 3D Printing and Coaxial Electrospinning Techniques

Abstract: We developed biodegradable drug-eluting prolapse mats using solution-extrusion 3D printing and coaxial electrospinning techniques. The mats were composed of polycaprolactone (PCL) mesh and lidocaine-, estradiol-, metronidazole-, and connective tissue growth factor (CTGF)-incorporated poly(lactic-co-glycolic acid) (PLGA) nanofibers that mimic the structure of the natural extracellular matrix of most connective tissues. The mechanical properties of degradable prolapse membrane were assessed and compared to comme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The spinning process parameters were set as follows: the receiving distance was 10–13 cm; the spinning voltage was 9–15 kV; the spinning temperature was 25 °C; the relative humidity was 65%; and the spinning speed of the main micro-push pump was 0.002–0.0030 mm/s. The obtained fiber film was dried at 45 °C for 8 h and sealed for subsequent experiments [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The spinning process parameters were set as follows: the receiving distance was 10–13 cm; the spinning voltage was 9–15 kV; the spinning temperature was 25 °C; the relative humidity was 65%; and the spinning speed of the main micro-push pump was 0.002–0.0030 mm/s. The obtained fiber film was dried at 45 °C for 8 h and sealed for subsequent experiments [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the animal data showed that the nanofibers did not induce any side effects and suggested that it can be effectively used for the treatment of pelvic organ prolapse repair [162]. The three-dimensional (3D) printing of polycaprolactone/nano-hydroxyapatite using an extrusion-based printer showed that drug-eluting PCL/nHA screws eluted increased stages of antimicrobial ceftazidime and vancomycin for 14 days [163].…”
Section: Drug-eluting Implant and 3d Printingmentioning
confidence: 99%
“…The results showed that 40% growth factor was released from FB-PL fiber membranes on the first d and 80% on the 7th d [84]. CTGF is unstable in a highly oxidized diabetic wound environment, and the use of nanofiber membranes loaded with CTGF can improve its stability and promote diabetic wound healing [99]. Augustine mixed PVA aqueous solution with CTGF solution to prepare PVA solution (6%, w/v) containing CTGF (0.1wt%).…”
Section: Drugs/synthetic Polymer Electrospun Fibersmentioning
confidence: 99%